The Impact of Ownership Structure on Real Earning Management- an Empirical Study on Industrial Companies Listed in Abu Dhabi Stock Exchange - رحال, ياسر; عفراء زحلوط (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research aimed to examine the impact of ownership structure on real earning management in industrial companies listed in Abu Dhabi stock exchange in the period between 2017-2021. in order to measure ownership structure the research use four variables, which are ownership concentration and government ownership and institutional ownership and foreign ownership. to achieve the goal of this research and examine the hypotheses multiple linear regression was used. The results of this study concluded that there is a negative significant effect of the government ownership and the foreign ownership on the dependent variable real earning management, which means that the increase of government and foreign ownership causes to decrease of real earning management. also, this study found that there is no effect of the ownership concentration and the institutional ownership on real earning management.